2004
DOI: 10.1261/rna.5212604
|View full text |Cite
|
Sign up to set email alerts
|

The Neurospora crassa CYT-18 protein C-terminal RNA-binding domain helps stabilize interdomain tertiary interactions in group I introns

Abstract: The Neurospora crassa mitochondrial tyrosyl-tRNA synthetase (CYT-18 protein) promotes the splicing of group I introns by stabilizing the catalytically active RNA structure. To accomplish this, CYT-18 recognizes conserved structural features of group I intron RNAs using regions of the N-terminal nucleotide-binding fold, intermediate ␣-helical, and C-terminal RNA-binding domains that also function in binding tRNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…To account for cleavages in P5 on the opposite end of the intron RNA, the C-terminal domain of the other subunit (Subunit A) must be located in proximity to the L9-P5 tertiary interaction. These locations explain previous findings that CYT-18’s C-terminal domain can suppress mutations that weaken both the L2-P8 and L9-P5 tertiary interactions (15) and that small deletions in Ins2, which helps orient P9, have more severe effects in the C-terminally truncated than in the full-length protein (17). The C-terminal domain can also compensate for mutations in several other regions of the intron that may indirectly affect the relative orientation of the core domains or positioning of P2 or P8 (15).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…To account for cleavages in P5 on the opposite end of the intron RNA, the C-terminal domain of the other subunit (Subunit A) must be located in proximity to the L9-P5 tertiary interaction. These locations explain previous findings that CYT-18’s C-terminal domain can suppress mutations that weaken both the L2-P8 and L9-P5 tertiary interactions (15) and that small deletions in Ins2, which helps orient P9, have more severe effects in the C-terminally truncated than in the full-length protein (17). The C-terminal domain can also compensate for mutations in several other regions of the intron that may indirectly affect the relative orientation of the core domains or positioning of P2 or P8 (15).…”
Section: Discussionsupporting
confidence: 79%
“…Mt TyrRSs are structurally homologous to the bacterial enzymes, and CYT-18 uses both its N-terminal catalytic and C-terminal tRNA-binding domains to bind group I intron RNAs (1315). However, group I intron splicing activity has been found only for the mt TyrRSs of Pezizomycotina, filamentous fungi that includes the model organisms Neurospora crassa , Aspergillus nidulans , and Podospora anserina , as well as important human pathogens, such as Histoplasma capsulatum, Coccidioides posadasii , and Aspergillus fumigatus (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial tyrosyl-tRNA synthetase CYT-18 from N. crassa is a bifunctional protein, which, in addition to aminoacylation of its cognate tRNA, has also adapted to facilitate folding of N. crassa mitochondrial group I introns via stabilization of the RNA tertiary interactions 47; 48; 49. Although biochemical studies indicated that the protein recognizes a tRNA-like structure within group I introns 47, recent crystallographic studies indicate that the protein uses completely different binding surfaces to interact with tRNA and group I intron RNAs 49.…”
Section: Discussionmentioning
confidence: 99%
“…Like its bacterial counterparts, CYT-18 functions as a homodimer, with each dimer binding either one molecule of tRNA Tyr or group I intron RNA [25] [28] . CYT-18 binds group I introns by using both its N-terminal catalytic domain and CTD, but only some introns require the CTD for RNA splicing [29] [31] .…”
Section: Introductionmentioning
confidence: 99%